The Use of Mobile Phone Technology in Teaching and Learning for Primary School Pupils During Covid-19 School Closure in Tanzania - Kafanabo, Eugenia (Papers in Education and Development, 2024)
This study investigated the use of mobile phone technology as a mitigation strategy for facilitating teaching and learning during the unprecedented COVID-19 pandemic-induced school closures in Tanzania. Employing an interpretive qualitative approach and a case study design informed by the Framework for the Rational Analysis of Mobile Education (FRAME), the study involved eleven (11) participants, encompassing one head teacher, three subject teachers, and seven parents. Data were collected through semi-structured interviews and documentary reviews and subsequently analysed using content and thematic analysis techniques. Findings revealed a sense of shock among parents and teachers due to the unforeseen closure of schools, but they promptly embraced mobile phones as a means to sustain students’ learning. These devices facilitated the exchange of learning materials via text messages, calls, social media, and emails. However, limitations in instructional skills and financial constraints for smartphone purchase and internet connectivity among parents posed significant challenges. The study recommends collaborative efforts between the government and other stakeholders to establish a robust online learning infrastructure that can ensure educational continuity during unforeseen school closures. Keywords: Mobile phone, technology, primary school, teachers, parents, Tanzania